Factors Determining Food Safety in Cuban Municipalities: Limitations and Capacities for Chain Approach Management - Gamboa Costa, Abel; Loret de Mola López, Enrique; Escalona Fernández, Yordanis; González Torres, Iris María; González Fontes, Ramón (Agrisost ISSN 1025-0247, 2018)
The aim of this paper is to identify the most commonly recognized determining factors of food safety, according to the dimensions established at the municipal scale; and secondly, to assess the capacities and limitations for chain approach management, in Cuba. Various national and international related methods, laws, programs, and policies were examined. The documentary review resulted in the classification of 10 factors, including four dimensions: availability (4), access (3), stability (1), and food use (2). The most commonly recognized factors by 16 authors were, 1) income level, 2) food prices, 3) local food production, 4) basic sanitation. A 5th factor was included, according to the authors’ criteria about the characteristics of the Cuban scenario: seasonality of crops and food items. They were linked to the agro-food chain through examples derived from the implementation of business projects and initiatives. It was concluded that the factors that determined access in terms of consumer market demand top priority in terms of municipal development strategies and Management of Municipal Administrations. Meanwhile, the limitations to apply this approach are mainly the contradictions between sector and local development.
Keywords: food safety; agro-food chains; public policies; municipal government